Anion-Exchange Distribution Studied of Lighter Rare Earth Metal Ions in Sodium Nitrite Organic Solvent-Water Media - Bhardwaj, Archana; Bhardwaj, S.D. (Asian Journal of Chemistry, 2010)
Anion-exchange equilibrium distribution coefficient of some lighter rareearth metal ions has been studied in aqueous sodium nitrite and sodiumnitrite-organic solvent water media using Dowex-1-X8 in nitrate form. Outof the less common metal ions studied, U(VI) gave very high distributionvalue followed by lighter rare earth. High KD values were expected formetal forming stabler metal-nitrite complexes.